EDUCATION OF THE SPIRITUAL AND MORAL PERSONALITY OF STUDENTS THROUGH THE STUDY OF UZBEKISTAN FOLK MUSIC AND CULTURAL HERITAGE - Shokirkhonov Bakhtiyorkhon Botirkhonovich (Web of Journals Publishing, 2025)
This article discusses in detail the issues of educating the spiritual and moral personality of students through the study of Uzbek folk music and cultural heritage.
Keywords: Tradition, music, culture, creativity, personality, morality, education, process, event, student, activity.